Apparatus Developments of Ultrasonic Vibration-Assisted Microabrasive Waterjet Polishing - Rongguo Hou; Tao Wang; Zhe Lv; Yansen Feng (Advances in Materials Science and Engineering)
The experiment apparatus of ultrasonic vibration-assisted microabrasive waterjet polishing is developed. The simulation model of ultrasonic nozzle is analyzed with the help of ANSYS software. The simulation result shows that the ultrasonic vibration leads to a good result that the maximum frequency with the value of 20908 Hz is obtained at the outlet of ultrasonic nozzle, and the vibration type is axial mode. Then the vibration frequency and amplitude of the developed experiment apparatus are tested using the ultrasonic transducer impedance analyzer and the laser displacement sensor. The measured result indicates that the vibration frequency is 19099 Hz and the amplitude is 22 μm, which means the experiment apparatus is well developed and satisfies the work requirements. The verifying experimental result shows that the ultrasonic vibration helps to enhance the machining ability of the abrasive waterjet, and the removal material volume and erosion depth are increased obviously.